PSYCHOLOGICAL WELL-BEING GURU NON-PLB DI SLB - Natalie Angel Lyke Batoek; Yeni Damayanti; Mernon Yerlinda C. Mage; R. Pasifikus Ch. Wijaya (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Psychological well-being is a fundamental pillar that ensures the sustainability of teachers' careers and the quality of instruction. However, educators with non-special education (non-PLB) backgrounds who work in Special Needs Schools (SLB) face significant challenges. These teachers often experience mental stress and technical obstacles due to limited specific knowledge in guiding children with special needs. This study aims to explore the picture of psychological well-being and identify the determinants that influence it in the SLB Negeri Pembina Kupang environment. Using descriptive qualitative methods, this study collected data through semi-structured interviews with four non-PLB teachers with less than five years of service, which were analyzed in depth using thematic analysis procedures. The research findings indicate that psychological well-being is significantly influenced by internal factors, including perseverance, resilience, emotional regulation skills, motivation for personal growth, and the meaning of the profession as a life calling that provides emotional satisfaction from student progress. In addition, external factors such as strong social support from colleagues, the principal, and parents are also crucial elements. The main conclusion is that the psychological well-being of these educators is the result of a dynamic interaction between personal capacity and socio-environmental support. These findings recommend the need for mental health strengthening programs for non-special education teachers to ensure the creation of a higher-quality inclusive education ecosystem. ABSTRAK Kesejahteraan psikologis merupakan pilar fundamental yang menjamin keberlanjutan karier serta kualitas instruksional guru, namun tantangan besar dihadapi oleh tenaga pendidik berlatar belakang non-pendidikan luar biasa (non-PLB) yang bertugas di Sekolah Luar Biasa (SLB). Para guru ini sering kali mengalami tekanan mental dan hambatan teknis karena keterbatasan pengetahuan spesifik dalam membimbing anak berkebutuhan khusus. Penelitian ini bertujuan untuk mengeksplorasi gambaran kesejahteraan psikologis serta mengidentifikasi faktor-faktor determinan yang memengaruhinya di lingkungan SLB Negeri Pembina Kupang. Menggunakan metode kualitatif deskriptif, penelitian ini mengumpulkan data melalui teknik wawancara semi-terstruktur terhadap empat guru non-PLB dengan masa pengabdian kurang dari lima tahun, yang dianalisis secara mendalam menggunakan prosedur analisis tematik. Temuan penelitian menunjukkan bahwa kesejahteraan psikologis dipengaruhi secara signifikan oleh faktor internal, yang meliputi aspek ketekunan, resiliensi, kemampuan regulasi emosi, motivasi pertumbuhan pribadi, serta pemaknaan profesi sebagai panggilan hidup yang memberikan kepuasan emosional atas kemajuan siswa. Selain itu, faktor eksternal berupa dukungan sosial yang kuat dari rekan sejawat, kepala sekolah, dan orang tua siswa turut menjadi elemen krusial. Sebagai simpulan utama, kesejahteraan psikologis para pendidik ini merupakan hasil interaksi dinamis antara kapasitas personal dan dukungan lingkungan sosial-lingkungan. Temuan ini merekomendasikan perlunya program penguatan mental bagi guru non-PLB guna memastikan terciptanya ekosistem pendidikan inklusif yang lebih berkualitas.